In vogue: demand for scholarly publications among academic librarians. Issue 6 (13th August 2018) - Quagraine, Nana Tuhufo; Agyekum, Baffour Ohene
Abstract : Purpose: The lack of a country-wide data on the extent to which academic librarians in Ghana publish combined with perceived publishing challenges as indicated by a number of scholars including Opoku (2012) leaves much to be desired. Therefore, the purpose of this paper is to seek the views of professional librarians in Ghana on the subject. Design/methodology/approach: Using a sample size of 45 out of 50 academic librarians who make up the membership of the Consortium of Academic and Research Libraries, the study employed the descriptive survey research strategy in identifying the prospects and challenges associated with academic publications among librarians in Ghana. Findings: Opportunities for growth, institutional encouragement, requirements for promotion, and opportunities for research training are some of the factors that motivated academic librarians to publish in scholarly journals notwithstanding the pressures to perform their professional duties. Challenges often encountered included lack of research grants, high rejection rate of publishing agencies, lack of research skills and difficulty in getting access to research journals. Practical implications: On the basis of the above, the establishment of research fund and an award scheme for persons or units with the highest number of publications among others are recommended. Originality/value: With the exception of cited works, all other forms of this research output are the handiwork of the researchers and have neither been a reproduction of existing research nor ever published in any other journal.